Satellite Coordinates from Ephemeris Data - Ataiwe, Tariq N.; Khalaf, Abbas Z.; Mohammed, I H (International Journal of Scientific Research in Civil Engineering, 2019)
This research aims to illustrate the process of reading the orbital parameters and computing the satellite coordinates from navigation messages. The data gathered using smartphone Huawei p 10. A MATLAB software package for GPS ephemeris data processing and reading is presented in this paper. The ephemeris data processing and its theoretical background are introduced first. Then, the advantages and limitations of using ephemeris data to compute orbital parameters are identified. Finally, the software workflow is briefly explained.